Levels of e-HRM adoption in subsidiaries of a US multinational corporation: the mediating role of power, politics and institutions. (1st January 2013) - Burbach, Ralf; Royle, Tony
Despite the purported advantages of electronic HRM (e-HRM) in assisting strategic decision making, few organisations appear to fully capitalise on e-HRM. This article explores the mediating role of power and politics on the levels of e-HRM utilisation in the German and Irish subsidiaries of a US multinational corporation (MNC). The research comprised 25 in-depth interviews with 15 key stakeholders in the case study firm. Key findings highlight that e-HRM adaptation in MNC subsidiaries is affected by the institutional contexts within which the organisation operates, as well as a set of micro-political and power relationships within the broader political structure of the MNC and as such are capable of curbing a multinational's capacity to disseminate human resource including e-HRM practices from the country of origin to its subsidiaries. In particular, resource power derived from strategic capabilities may be employed by subsidiary actors to shape the manner in which e-HRM is utilised.